Arthropod facilitation mediated by abandoned dead domatia. Issue 1 (20th January 2021) - Novais, Samuel; Cristóbal‐Perez, E. Jacob; Aguirre‐Jaimes, Armando; Quesada, Mauricio
Abstract: In ant–plant mutualistic interactions, plants provide shelter (domatia) and/or food to ants and in exchange, and ants provide protection against herbivores. After plant tissue senescence, ants are expected to abandon dead domatia, leaving these empty spaces available for other arthropods. In this study, we tested for the role of the mutualistic interaction between Cordia alliodora and Azteca pittieri in promoting new habitats for arthropods through abandoned dead domatia. We predicted that species richness, abundance, and colonization frequency of secondary arthropods would be greater in dead branch domatia (dead domatia) compared with live branch domatia (live domatia). During March 2019, we selected 38 C. alliodora trees in a Mexican tropical dry forest. For each tree, we collected five live and five dead domatia, for 380 domatia in total. We found six morphospecies of secondary arthropods colonizing live domatia, while 42 were present in dead domatia. Ants were the most species‐rich group (10 species) in abandoned dead domatia and utilized them as nesting sites (25 nests). Secondary arthropod species richness, abundance, and colonization frequency were greater in dead domatia compared with live domatia. We concluded that the Azteca–Cordia mutualistic interaction is an important habitat facilitator by promoting new habitats for arthropods through abandoned dead domatia.